2020
DOI: 10.1097/j.pain.0000000000001733
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cell-derived GABAergic interneuron transplants attenuate neuropathic pain

Abstract: Neuropathic pain causes severe suffering, and most patients are resistant to current therapies. A core element of neuropathic pain is the loss of inhibitory tone in the spinal cord. Previous studies have shown that foetal GABAergic neuron precursors can provide relief from pain. However, the source of these precursor cells and their multipotent status make them unsuitable for therapeutic use. Here, we extend these findings by showing, for the first time, that spinally transplanted, terminally differentiated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…HESC-MGE progenitor cells have also been transplanted into the mouse spinal cord and shown to alleviate central neuropathic pain following SCI [50]. Most recently, we have generated matured functional GABAergic neurons from hiPSC and transplanted them into the spinal cord of mice with established peripheral nerve injury, providing pain relief for up to two months without damaging the spinal cord or affecting the mice motor function [51]. Given the potent analgesic effect of the GABAergic transplants and the resultant potential for its clinical use, a long-term study is currently underway to ascertain the efficacy and safety of this procedure.…”
Section: Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…HESC-MGE progenitor cells have also been transplanted into the mouse spinal cord and shown to alleviate central neuropathic pain following SCI [50]. Most recently, we have generated matured functional GABAergic neurons from hiPSC and transplanted them into the spinal cord of mice with established peripheral nerve injury, providing pain relief for up to two months without damaging the spinal cord or affecting the mice motor function [51]. Given the potent analgesic effect of the GABAergic transplants and the resultant potential for its clinical use, a long-term study is currently underway to ascertain the efficacy and safety of this procedure.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…Whether the discrepancy in the results can be attributed to the difference in immunocompetency of the mouse models is unclear but would benefit from further investigation. Similarly, chronic neuropathic pain cell therapy studies used immunosuppressed animals [50,51] which may affect the results. Whilst transplantation studies using syngenic fetal mouse material suggest this will not affect analgesia, given the important role of immune cells in pain pathogenesis [193,194] or CNS regeneration, further investigation is needed to establish the potential effect of immunosuppression.…”
Section: Cns Microenvironmentmentioning
confidence: 99%
“…Different considerations include NSCs, directed spine neural progenitors, or more complex anatomically matched cells and circuitry to accelerate repair and reproducible recovery. Along with functional recovery, the ability comes to regulate spinal mechanisms of pain, recently achieved by transplantation of inhibitory interneurons (Manion et al, 2020).…”
Section: Gastruloids Circuitoids and Assembloidsmentioning
confidence: 99%
“…Specifically for human therapies of the trunk and spine (Figures 4, 5), information arising from developmental neurotechnologies, including embryology, can now be analyzed to inform and improve treatments beyond trauma. Most recently, this includes neuromuscular disorders such as ALS and myasthenia gravis (reviewed in Sances et al, 2016;Faustino Martins et al, 2020), neural tube defects such as spina bifida that can be related to the Pax3 gene (Sudiwala et al, 2019), neurocristopathies such as Hirschsprung's disease resulting from NCC migration defects (Fattahi et al, 2016;Workman et al, 2017), neurodegeneration or demyelinating process originating in the CNS (Garden and La Spada, 2012), and sensory disorders such as neuropathic pain (Manion et al, 2020). We expect that human stem cell developmental neurotechnologies will continue to play an essential role in understanding and treating these disorders through the elementary discovery of fundamental processes, in vitro models, and scalable high throughput platforms for drug testing, as well as by supplying an unlimited customized cell resource for replacement therapies.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Here, Manion et al (17) has recently overcome this problem by showing that terminally differentiated human induced pluripotent stem cell-derived GABAergic (iGABAergic) neurons transplanted into the spinal cord significantly reduced NPP symptoms of mice subjected to spinal nerve injury. They found that iGABAergic neurons can survive in the spinal cord of NPP mice, and these cells were able to alleviate pain long term (~2 months) with a single treatment, demonstrating that this translational strategy is a viable option for the alleviation of established NPP.…”
Section: Cell Transplantation Of Gabaergic Interneuronsmentioning
confidence: 99%